Malaysia's development challenges : graduating from the middle - Hill, Hal, 1948-; Tham, Siew Yean.; Ragayah Haji Mat Zin. (Milton Park, Abingdon, Oxon : Routledge, 2011)
'This book identifies and discusses the key aspects of Malaysia's current development policy challenges. Subjects covered include technology, education and skills, the promotion of entrpreneurship, social issues, monetary policy and governance issues, with the discussion of each subject empirically rich, rooted in Malaysia's development experience, and forward looking.'--Publisher's description.
Includes bibliographical references and index.
Keywords: Economic development -- Malaysia; Malaysia -- Economic conditions; Malaysia -- Economic policy